2017
DOI: 10.1002/joa3.12016
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation and cryptogenic stroke. What is the current evidence? Role of electrocardiographic monitoring

Abstract: The diagnosis of cryptogenic stroke is made by exclusion. However, current evidence supports the role of atrial fibrillation episodes as a cause of this condition. Prospective data have demonstrated the benefits of long‐term electrocardiographic monitoring to identify atrial fibrillation in association with cryptogenic stroke. This aim of this article was to analyze the contemporary evidence for the possible relationship between atrial fibrillation and cryptogenic stroke and the role of continuous electrocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…ICMs should therefore be considered more often in the evaluation of cryptogenic ischaemic events. 5,30,31 Currently only a minority of cryptogenic stroke patients are screened with long-term ECG because this method is still not routinely available in clinical practice due to high costs. 32 Another reason is that the cryptogenic stroke patients group is very heterogenic regarding aetiology and only a minority have cardioembolism due to AF.…”
Section: Discussionmentioning
confidence: 99%
“…ICMs should therefore be considered more often in the evaluation of cryptogenic ischaemic events. 5,30,31 Currently only a minority of cryptogenic stroke patients are screened with long-term ECG because this method is still not routinely available in clinical practice due to high costs. 32 Another reason is that the cryptogenic stroke patients group is very heterogenic regarding aetiology and only a minority have cardioembolism due to AF.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, none of our patients showed heart abnormalities in routine examination, which might be explained by the following reasons. First, in a previous report, only 3% of AF cases were diagnosed using 24-hour ECG in cryptogenic stroke, but the detection rate increased to 30% with 36-month monitoring ( 52 ). Elevated P terminal force v1, a marker of early atrial pathological change, was also related to embolic stroke ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is desirable that ECG monitoring initiated shortly after ESUS be prolonged, especially in the subpopulation with additional signs of atrial disease [17][18][19][20][21][22]. Supplementary diagnostic procedures should be initiated as soon as possible following the occurrence of stroke, in order to maximise the benefits of potentially indicated anticoagulation.…”
Section: Therapeutic Problemmentioning
confidence: 99%